Effect of the High-FODMAP Diet on Bowel Preparation for Colonoscopy: A Multicenter, Prospective Cohort Study - Peng Cheng; Ruijun Ma; Shuling Wang; Jun Fang; Zhengrong Zhong; Yu Bai; Xiangjun Meng; Zhaoshen Li (Gastroenterology Research and Practice)
Background. Optimal bowel preparation for colonoscopy is fundamental to a successful examination. The FODMAP diet can increase the content of intestinal water and gas, but its impact on bowel cleanliness and bubbles has not been reported. This study was therefore aimed at evaluating the effect of the FODMAP diet on the quality of bowel preparation and the adenoma detection rate (ADR). Methods. This was a multicenter, prospective cohort study involving consecutive patients who underwent colonoscopy in two centers in China. Patients were assigned to one of two groups: high-FODMAP or nonhigh-FODMAP diet. ODMP Software was used for the identification of FODMAP diet types. The primary outcome was ADR; secondary outcomes were the quality of bowel preparation, measured by the Boston bowel preparation scale and bubble scores. Results. There were 365 patients included. Patients in the high-FODMAP-diet group showed poor bowel cleansing efficacy: BBPS≥6 in 76.8% vs. 90.3% (P<0.01) and bubble scores of 2.42±1.69 vs. 1.32±1.63 (P<0.001). The intubation time was significantly longer in the high-FODMAP-diet group (7.07±5.18 vs. 5.46±3.05 min; P=0.002). The High-FODMAP diet was an independent risk predictor for inadequate bowel preparation. There were no statistically significant differences in ADR between the two dietary groups. Conclusion. The high-FODMAP diet significantly reduced the quality of bowel preparation. We recommend the consumption of nonhigh-FODMAP diet in bowel preparation as a reference standard for dietary regimen. This method was effective, flexible, referable, and well tolerated, which could help to provide patients a valuable dietary guidance in bowel preparation.